2015
DOI: 10.1016/j.ejrad.2014.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial chemoembolization in soft-tissue sarcoma metastases to the liver – The use of imaging biomarkers as predictors of patient survival

Abstract: Background The clinical management of patients with metastatic soft-tissue sarcoma of the liver is complicated by the paucity of reliable clinical data. This study evaluated the safety profile, survival outcome as well as the role of imaging biomarkers of tumor response in metastatic soft-tissue sarcoma (mSTS) of the liver treated with conventional transarterial chemoembolization (cTACE). Materials/methods This retrospective analysis included 30 patients with mSTS of the liver treated with cTACE. The safety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 31 publications
1
27
0
1
Order By: Relevance
“…Indeed, several works have shown the predictive value of tumor segmentation–based quantitative analysis in patients with HCC (24,25). This was also done for metastatic disease in the liver, where it was shown that the same 3D methods used in our work had improved survival prediction when compared with the one- and two-dimensional methods (32,33,39). …”
Section: Discussionmentioning
confidence: 71%
“…Indeed, several works have shown the predictive value of tumor segmentation–based quantitative analysis in patients with HCC (24,25). This was also done for metastatic disease in the liver, where it was shown that the same 3D methods used in our work had improved survival prediction when compared with the one- and two-dimensional methods (32,33,39). …”
Section: Discussionmentioning
confidence: 71%
“…Second, a volumetric assessment addresses the discordance between lesion diameter or area and volume of tumor tissue—a limitation associated with one-and two-dimensional enhancement-based criteria (mRECIST and EASL, respectively) (14,15,39). Both criteria examine one axial section, which often is not representative of the entire tumor and could explain why mRECIST and EASL were poor biomarkers for survival in our study and other studies (11,14,17,18). Volumetric enhancement–based criteria, however, measure the entire tumor and can account for the heterogeneous, nonspherical necrosis that embolotherapy induces (15,39).…”
Section: Discussionmentioning
confidence: 74%
“…Volumetric measurements of tumor enhancement are more representative of tumor necrosis and have been shown to help predict survival (11,14,17,18). In general, volumetric analysis has been applied on a lesion-by-lesion basis.…”
mentioning
confidence: 99%
“…Quantitative and functional evaluation of hepatic lesions provide a more comprehensive assessment of tumor response, as these metrics consider changes in the whole tumor as opposed to conventional criteria which assess the tumor in a single axial plane. In addition, former studies have shown a higher correlation between these volumetric metrics with overall survival and histopathological evaluation compared with anatomic metrics [13], [14], [16], [22], [28], [29]. Yet, to date, only a few studies have assessed similar application of both volumetric and anatomic metrics for hypo-vascular liver metastases.…”
Section: Discussionmentioning
confidence: 99%